Evaluation of two extractants for the estimation of available potassium, Calcium and magnesium in acid soils under rubber - Sudhakumari B; Joseph Mercykutty; Karthikakuttyamma M; Mathew M (Indian Journal of Natural Rubber Research, 1994)
Two extractants were compared for the estimation of available K, Ca and Mg in acid soils under rubber. Wide variation in soil K, Ca and Mg was recorded between the samples. Numerically higher values were obtained for available K with ammonium acetate extraction. For Ca and Mg more quantity was extracted with Morgans extractant. Correlations between soil test values and corresponding leaf nutrient concentrations indicated that both extractants are equally good for evaluating the availability of K and Ca. Considering the non-corrodable nature and being the universal extractant, ammonium acetate was found to be the better choice. A better extractant has to be identified for available Mg.
Keywords: Ammonium acetate; Available nutrients; Exchangeable ions; Hevea brasiliensis; Sodium acetate